2021
DOI: 10.3389/fmicb.2021.789765
|View full text |Cite
|
Sign up to set email alerts
|

PmtA Regulates Pyocyanin Expression and Biofilm Formation in Pseudomonas aeruginosa

Abstract: The opportunistic pathogen Pseudomonas aeruginosa expresses a small molecular weight, cysteine-rich protein (PmtA), identified as a metallothionein (MT) protein family member. The MT family proteins have been well-characterized in eukaryotes as essential for zinc and copper homeostasis, protection against oxidative stress, and the ability to modify a variety of immune activities. Bacterial MTs share sequence homology, antioxidant chemistry, and heavy metal-binding capacity with eukaryotic MTs, however, the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Flagella-mediated swimming, type IV pili-mediated rubbing, pyocyanin, and oxidative phosphorylation are known to be involved in biofilm formation. 33 , 50 Therefore, we assumed that biofilm formation by this strain was also reduced. To verify this hypothesis, we investigated the role of PA0715 in biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flagella-mediated swimming, type IV pili-mediated rubbing, pyocyanin, and oxidative phosphorylation are known to be involved in biofilm formation. 33 , 50 Therefore, we assumed that biofilm formation by this strain was also reduced. To verify this hypothesis, we investigated the role of PA0715 in biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilm formation capacity was assessed using a previously described method with slight modification. 32 , 33 Briefly, overnight cultures of PA01 were diluted 1:100 with LB broth and grown for an additional 3 h. Ten microliters of PAO1 bacterial suspension (adjusted to an OD 600 of 0.6) and 190 μL LB medium were transferred to 96-well flat-bottom microplates to make a final volume of 200 μL, and incubated at 37 °C for 72 h. Following incubation, the culture medium was removed. To exclude planktonic cells that might interfere with the interpretation of results, the bottom of the well plate was washed thrice with sterile 1× PBS buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Pyocyanin is a redox-active pigment that imposes oxidative stress on airway epithelial cells and mediates tissue damage and necrosis during lung infections 74 . Pyocyanin was also shown to cause death in G. mellonella infection model 75 , 76 . We have previously reported that the deletion of efhP completely abolished pyocyanin production in biofilm cells of FRD1, the alginate-producing strain of P. aeruginosa, grown at elevated Ca 2+ 17 .…”
Section: Discussionmentioning
confidence: 98%
“… 32 Besides drug resistance, PA biofilm formation has been reported to be associated in particular with pyocyanin (blue-green lipid-soluble pigment) expression. 33 , 34 On the contrary, no correlation between biofilm formation and drug resistance–or other virulence factors–has been reported, 34 suggestive of PA as a notorious biofilm producer and its continuous involvement in persistent chronic infections. Variation in the source of the isolates highlights the enormous burden of PA in the clinical settings, particularly in device-associated infections, which must be dealt with.…”
Section: Discussionmentioning
confidence: 99%